2004
DOI: 10.1177/1049731503254106
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Secondary Traumatic Stress Scale

Abstract: Objective: To describe the development and validation of the Secondary Traumatic Stress Scale (STSS), a 17-item instrument designed to measure intrusion, avoidance, and arousal symptoms associated with indirect exposure to traumatic events via one's professional relationships with traumatized clients. Method: A sample of 287 licensed social workers completed a mailed survey containing the STSS and other relevant survey items. Results: Evidence was found for reliability, convergent and discriminant validity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
782
9
27

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 604 publications
(884 citation statements)
references
References 24 publications
15
782
9
27
Order By: Relevance
“…The STSS fills a need for reliable and valid instruments specifically designed to measure the negative effects of social work practice with traumatized populations. The instrument may be used to undertake empirical investigation into the prevention and amelioration of secondary traumatic stress among social work practitioners (Bride, Robinson, & Charles, 2003). 19 In summary, the literature identified that CF is a serious issue in nursing specifically those working in hospice.…”
Section: Compassion Fatigue Measurementmentioning
confidence: 99%
“…The STSS fills a need for reliable and valid instruments specifically designed to measure the negative effects of social work practice with traumatized populations. The instrument may be used to undertake empirical investigation into the prevention and amelioration of secondary traumatic stress among social work practitioners (Bride, Robinson, & Charles, 2003). 19 In summary, the literature identified that CF is a serious issue in nursing specifically those working in hospice.…”
Section: Compassion Fatigue Measurementmentioning
confidence: 99%
“…A Cronbach's alpha coefficient of 0.92, has been identified by Neff (2003b) along with the following for the subscales; isolation (0.79); self-judgment (0.77); over identification (0.81); self-kindness (0.78); common humanity (0.80); and mindfulness (0.75) [52]. The third section of the questionnaire, the Secondary Traumatic Stress Scale (STSS), is the only instrument that has been designed to assess Secondary Traumatic Stress (STS) [36]. The symptoms of STS are virtually identical to those of Post-Traumatic Stress Disorder (PTSD) and include symptoms of ' Avoidance', 'Intrusion' and ' Arousal' [35].…”
Section: Instrumentsmentioning
confidence: 99%
“…The STSS and SCS scores for each of the participants were calculated and interpreted using the score categories developed by the creators of the two tools [36,52]. The intention was to select from those who had completed the 'expression of interest' form, those participants who typified a particular score in both the STSS and SCS.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations